If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + -8 = -11 Reorder the terms: -8 + 3t = -11 Solving -8 + 3t = -11 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 3t = -11 + 8 Combine like terms: -8 + 8 = 0 0 + 3t = -11 + 8 3t = -11 + 8 Combine like terms: -11 + 8 = -3 3t = -3 Divide each side by '3'. t = -1 Simplifying t = -1
| x/3-6=10 | | y-18+y+x=180 | | 7x-5=-2x+4 | | -2y+14=3x | | 6h+5(3)=45 | | 5x+3(x-4)+12=2(4x+3) | | 2x+14=3x-31 | | 9r-9=-342 | | 4/3x-10=24 | | 7k-8(10)=45 | | -4=-9+v | | 4b-7=101 | | 45(n+6)=35n | | 2.56=x/2 | | -7=w+8 | | 2p+7=-53 | | (Y/6)4 | | 4x+1x+25+3x-5=2y-12 | | 8(9)+7a=79 | | 4c+6=-130 | | 5x-26=3x+20 | | 3+2(x+2)=9+3x | | (Y/-15)5 | | -8(x-2)=24 | | 16x^4-8x^2=0 | | -4x^2+5x=y | | =.59=x/4-0.09 | | 17(x+6)=306 | | 8i(9-4I)= | | 6.5=-4(-n-4) | | 3*(2x+2)=4*(x+8) | | 14x+2=16+7x |